(untitled) (Journal of actual problems of jurisprudence, 2022)
The concept of the legal policy of the Republic of Kazakhstan until 2030 states: "The balance of punitive, restorative and preventive means of criminal law regulation is important. In this context, the maximum focus of criminal legislation on the restoration of violated rights, the prevention of new offenses by both convicts and other persons will increase. When forming sanctions of criminal law norms, the principle of their proportionality of the degree of public danger and the nature of the offense should be strictly observed. " Nevertheless, as life shows, the measures taken by the state in the framework of the implementation of the concept are not enough to protect the family from spiritual and moral decay. If you open any news site, you will face data on violence against minors, women in the family in different parts of the country. Despite the adoption of the Law of the Republic of Kazakhstan of December 4, 2009 N 214-IV "On the Prevention of Domestic Violence" and its entry into force, the problem of domestic violence is still an acute, urgent topic (Law of the Republic of Kazakhstan of December 4, 2009 N 214-IV "On the Prevention of Domestic Violence"). Preventive activities of law enforcement agencies, various public organizations, non-profit organizations, centers do not produce appropriate results. According to 150 independent services, over 15 years they made 2.5 million calls. In 2020, 3377 domestic violence calls were received on the line. In 2021, the number of calls amounted to 226,455 units, of which 7184 calls came from children under 18 years old. (EL.KZ: https://el.kz/ru/news/obshestvo/kak_zashchitit_detey_ot_nasiliya_/). Keywords: domestic violence, family, domestic relations, crime, cause, situation, prevention, system of measures, conflict of interest, social situation, market economy, etc.